Kepemimpinan Kepala Madrasah Bertipe Demokratis Dalam Sistem Tata Kelola Pendidikan di MTs Wahdah Islamiyah Bone Bolango - Rajak, Ihan Abdul; G. Otaya, Lian; Solong, Nadjamuddin Petta (IAIN Manado, 2023)
The Leadership of the Madrasa Head is Democratic in the Education Governance System at MTs Wahdah Islamiyah Bone Bolango. This study aims to determine the leadership style of the head of the madrasah in the education governance system, which includes several aspects, including the head of the madrasah as a leader, the head of the madrasah as a motivator and innovator, the role of the head of the madrasah as a supervisor, the role of the head of the madrasah as a manager, and the role of the head of the madrasah as an educator in educational institutions. This research was conducted at Madrasah Tsanawiyah Wahdah Islamiyah Bone Bolango. This research uses qualitative descriptive methods. The research object was the head of the madrasah and all teachers in the Tsanawiyah Wahdah Islamiyah Madrasah Bone Bolango. This study used a sample of teachers who taught at Madrasah Tsanawiyah Wahdah Islamiyah Bone Bolango, with as many as ten people. The results showed that the leadership of the head of the madrasah in Madrasah Tsanawiyah Wahdah Islamiyah Bone Bolango is a democratic type of leadership so that in his leadership, a madrasah head always receives various kinds of suggestions and solutions, even criticism from multiple parties and seeks the best solution according to mutual agreement. The research results are expected to provide information and input materials for the madrasah, which is the place of research, as reference and evaluation material for other educational institutions, especially madrasahs in Bone Bolango.